A Partially Randomized Patient Preference Trial to Assess the Quality of Life and Patency Rate After Minimally Invasive Cardiac Surgery-Coronary Artery Bypass Grafting: Design and Rationale of the MICS-CABG PRPP Trial - Gong, Yichen; Wang, Xiaoxiao; Li, Nan; Fu, Yuanhao; Zheng, Hui; Zheng, Ye; Zhan, Siyan; Ling, Yunpeng (Frontiers in Cardiovascular Medicine, 2022)
Background: Minimally invasive cardiac surgery-coronary artery bypass grafting (MICS-CABG) has emerged as a safe alternative to standard cardiac surgery. However, treatment preferences can decrease the generalizability of RCT results to the clinical population (i.e., reduce external validity) and influence adherence to the treatment protocol and study outcomes (i.e., reduce internal validity). However, this has not yet been properly investigated in randomized trials with consideration of treatment preferences. Study Design: In this study, patients with a preference will be allocated to treatment strategies accordingly, whereas only those patients without a distinct preference will be randomized. The randomized trial is a 248-patient controlled, randomized, investigator-blinded trial. It is designed to compare whether treatment with MICS-CABG is beneficial in comparison to CABG. This study is aimed to establish the superiority hypothesis for the physical component summary (PCS) accompanied by the non-inferiority hypothesis for overall graft patency. Patients with no treatment preference will be randomized in a 1:1 fashion to one of the two treatment arms. The primary efficacy endpoints are the PCS score at 30 days after surgery and the overall patency rate of the grafts within 14 days after surgery. Secondary outcome measures include the PCS score and patency rate at different time points. Safety endpoints include major adverse cardiac and cerebrovascular events, complications, bleeding, wound infection, death, etc. Conclusions: This trial will address essential questions of the efficacy and safety of MICS-CABG. The study will also address the impact of patients’ preferences on external validity and internal validity.